Upaya Meningkatkan Keaktifan Dan Hasil Belajar IPS Melalui Model Discovery Learning untuk Siswa Sekolah Dasar - Iswan Riyadi; Sri Suwartini (Universitas Muhammadiyah Magelang, 2022)
The purpose of this study was to determine the extent to which the activeness and learning outcomes of elementary school students were increased through the Discovery Learning model. The method in this study was classroom action research.This classroom action research was conducted at SD N 1 Danguran Klaten. This research was conducted for 3 months starting from March to Mey 2021 The subjects in this study were 20 students at grade V. The steps of action research included planning, implementation, data collection, and reflection on each step for two cycles. The results of the study stated that students' understanding of the problem of ethnic and cultural diversity in Indonesia, in the first cycle of 7.01% and in the second cycle of 7.80%, was classified as good as well as about learning completion in the first cycle 74.82%. and in the second cycle it became 89.96%.